PERBEDAAN KOMITMEN ORGANISASIONAL BERDASARKAN KARAKTERISTIK INDIVIDU - Mutiara S. Panggabean (Universitas Trisakti, 2001)
The paper studies the comparablity of organizational commitment according to different individual characteristic consists of sexes, age, education, tenure, mamiage status and dependants. The organizational commitment is measured by three dimensions: continuance, affective, and normative commitments. The samples are students of the University of Indonesia and University of Trisakti. By using ANOVA and Post-Hoc Pair wise Muliple Comparison and Independent T-test, the study concludes that organizational commitment is differed based on individual characteristics on of sexes, age, education, tenure, marriage status and dependants. However, based on partial organizational commitment, the study includes that age, sexes, educational level, marriage status and total dependants show the distinction on affective commitment Cnly in educational level shows the difference on tenure.